Peran Literasi Keuangan Digital dalam Memitigasi Dampak Pinjaman Online dan Judi Online - Alfin Cahya Firmansyah (Jurnal Ekonomi dan Bisnis Digital, 2026)
The rapid development of digital technology has significantly expanded public access to technology-based financial services, including online lending (peer-to-peer lending). However, this convenience has also been accompanied by the increasing prevalence of online gambling, which frequently exploits digital financial services as a source of funding, leading to various economic, social, and legal challenges. This study aims to analyze the role of digital financial literacy in mitigating the adverse impacts of online lending and online gambling on Indonesian society. The research employs a normative juridical method using statute, conceptual, and case approaches. Data were collected through a comprehensive literature review of laws and regulations, scientific publications, official government reports, and relevant documents concerning the development of online lending and online gambling in Indonesia. The findings reveal that low levels of digital financial literacy constitute one of the primary factors contributing to individuals' vulnerability to online lending misuse and online gambling activities. Digital financial literacy plays a crucial role in enhancing public understanding of the benefits, risks, legality, and consequences of using digital financial services, thereby enabling individuals to make rational financial decisions, avoid illegal financial practices, and manage their finances sustainably. Therefore, strengthening digital financial literacy through collaboration among the government, regulators, educational institutions, financial service providers, and society represents an effective preventive strategy to reduce the negative impacts of online lending and online gambling while fostering a safe, inclusive, and sustainable digital financial ecosystem.